Pengaruh Perputaran Aset, Ukuran Perusahaan, Dan Leverage Terhadap Kinerja Keuangan Pada Perusahaan Bumn Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Natal, Desmon; Ananda, Rana Fathinah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study examines the influence of asset turnover, firm size, and leverage on the financial performance of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2021–2023 period. The research uses a quantitative approach. The study population consists of 27 SOEs listed on the Indonesia Stock Exchange from 2021 to 2023. The sampling technique employed is non-probability sampling, specifically saturated sampling. The total sample comprises 81 annual financial reports of SOEs. The data analysis method used in this study is multiple linear regression, conducted using SPSS software version 29, along with classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study show that asset turnover has no significant effect on financial performance. Firm size has a significant effect on financial performance. Leverage does not have a significant effect on the financial performance of SOEs listed on the Indonesia Stock Exchange during the 2021–2023 period.